Surgical management of rectovaginal fistula in a tertiary referral centre: many techniques are needed. (30th July 2013) - Tozer, P. J.; Balmforth, D.; Kayani, B.; Rahbour, G.; Hart, A. L.; Phillips, R. K. S.
Abstract Aim Surgery is the mainstay of treatment for rectovaginal fistula (RVF). Published success rates vary with initial success being around 50% rising to 80% with repeated surgery. Fistulae in Crohn's disease are more likely to recur. Method A retrospective study was performed of RVF repair carried out between 2003 and 2008 in a tertiary referral centre. Patients undergoing surgery for an RVF under the senior author during the study period were identified and their clinical notes were reviewed. Results Thirty‐five patients underwent 50 operations. The median age was 42 years and 83% were tertiary referrals. Two patients were lost to follow‐up. Healing occurred in 19 (58%) of 33 patients after a mean of 1.4 operations. The median time to success was 11 (2.5–48) months. The 'curative' group had an overall success of 73% (19 of 26). Seventy‐five per cent of non‐inflammatory bowel disease patients and 67% of those with Crohn's disease had successful treatment of the RVF. Twenty‐four of 35 patients (67%) underwent creation of a stoma. Sixteen of 24 (67%) were deemed fit for restoration of continuity. No demographic or disease related factors were found to influence healing. Conclusion Cure of RVF can be achieved by a range of surgical approaches including abdominal and anal. A variety of different anal techniques are necessary, depending on the integrity of the anal sphincter and the presence or absence of perineal descent/internal intussusception.